Analisis Perlindungan Hukum Atas Sengketa Medik Hak Pasien di Rumah Sakit dengan Pendekatan Win-win solution - Vivin Handoko; Muammar Fadillah; Wewe Suryani; Rara Afrieska; Maria Eka Patri Yulianti; Reny Suryanti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The development of healthcare services in Indonesia demands clear legal protection for patients' rights, especially in the resolution of medical disputes between patients and healthcare providers. However, the relationships formed in this context do not always run harmoniously, often leading to medical disputes. These disputes often arise between patients and healthcare providers due to patient dissatisfaction with the service outcomes, allegations of malpractice, or lack of communication between the parties. Legal protection of patients' rights is a central issue in resolving medical disputes. This study is a normative legal research. The analysis will focus on qualitative analysis by discussing regulations and literature related to Indonesian healthcare law. The win-win solution approach through mediation and restorative justice is an effective and fair mechanism for resolving medical disputes, as it emphasizes consensus, transparency, and relationship restoration. Commitment from all parties is needed to optimize this mechanism through enhancing mediator capacity, raising awareness of patients' rights, and improving the hospital complaint system.